2019
DOI: 10.1016/j.jid.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Nicastrin/miR-30a-3p/RAB31 Axis Regulates Keratinocyte Differentiation by Impairing EGFR Signaling in Familial Acne Inversa

Abstract: Nicastrin (NCSTN) mutations are associated with familial acne inversa (AI), and emerging evidences suggest that microRNAs (miRNAs) are involved in various skin diseases. However, whether NCSTN mutations affect miRNA levels and their subsequent signaling pathways in familial AI patients has not been studied. We aimed to elucidate the relationship between NCSTN mutations and familial AI pathogenesis by investigating differential miRNA expression and their related pathways. Combined with miRNA microarray data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…RAB31 promotes the degradation of activated epidermal growth factor receptor, leading to abnormal differentiation of keratinocytes, thereby implicating the miR-30a-3p-RAB31-epidermal growth factor receptor axis in hidradenitis suppurativa pathogenesis associated with NCSTN mutations related to familial hidradenitis suppurativa. 37 These findings suggest that dysregulation of c-secretase genes leads to impairment of the Notch signalling pathway, thereby inhibiting Toll-like receptor-activated macrophages by blocking the activation of transcription factors. Additionally, Notch signalling induces mitogen-activated protein kinase dephosphorylation, and inhibition of mitogen-activated protein kinase-dependent cytokine production ultimately leads to excessive activation of macrophages, resulting in hypersecretion of proinflammatory factors, abnormal differentiation of keratinocytes and induction of related clinical symptoms.…”
Section: The Role Of C-secretase Gene Dysfunction In Hidradenitis Supmentioning
confidence: 96%
See 1 more Smart Citation
“…RAB31 promotes the degradation of activated epidermal growth factor receptor, leading to abnormal differentiation of keratinocytes, thereby implicating the miR-30a-3p-RAB31-epidermal growth factor receptor axis in hidradenitis suppurativa pathogenesis associated with NCSTN mutations related to familial hidradenitis suppurativa. 37 These findings suggest that dysregulation of c-secretase genes leads to impairment of the Notch signalling pathway, thereby inhibiting Toll-like receptor-activated macrophages by blocking the activation of transcription factors. Additionally, Notch signalling induces mitogen-activated protein kinase dephosphorylation, and inhibition of mitogen-activated protein kinase-dependent cytokine production ultimately leads to excessive activation of macrophages, resulting in hypersecretion of proinflammatory factors, abnormal differentiation of keratinocytes and induction of related clinical symptoms.…”
Section: The Role Of C-secretase Gene Dysfunction In Hidradenitis Supmentioning
confidence: 96%
“…Moreover, recent studies show that NCSTN mutations lead to decreased microRNA (miR)‐30a‐3p levels, which negatively regulate RAB31 expression. RAB31 promotes the degradation of activated epidermal growth factor receptor, leading to abnormal differentiation of keratinocytes, thereby implicating the miR‐30a‐3p–RAB31–epidermal growth factor receptor axis in hidradenitis suppurativa pathogenesis associated with NCSTN mutations related to familial hidradenitis suppurativa …”
Section: Relationship Between Dysfunctional γ‐Secretase Genes and Hidmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small noncoding RNAs functioning as biological regulators in some skin diseases . In previous study, we found that miR‐100‐5p was downregulated in both familial HS and keratinocyte‐specific Ncstn ‐knockout ( Ncstn ΔKC ) mice . As the AKT‐related pathway is one target of miR‐100‐5p, whether decreased miR‐100‐5p expression could affect skin cells through this pathway in familial HS with a NCSTN mutation remains to be proved.…”
mentioning
confidence: 99%
“…This study was approved by Medical Ethics Committee (2017‐KY‐015) and Animal Care Ethics Committee of the Institute of Dermatology, Chinese Academy of Medical Sciences, and was performed in accordance to the principles of the Declaration of Helsinki. Five Chinese patients with HS and NCSTN mutations and five healthy volunteers (control group) were enrolled. Skin biopsies were obtained from the lesions of the familial HS group and healthy individuals undergoing cosmetic surgical procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation